RESILIENSI KORBAN BULLYING VERBAL PADA SISWI KELAS VIII SMP NEGERI 2 KOTA PONTIANAK - Farenti, Sheila Aisyah; Agustine, Friska Amellia (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2025)
This study aims to determine the types of verbal bullying and forms of resilience owned by victims of verbal bullying at SMP Negeri 2 Pontianak City. The method used in this research is a qualitative research method of case study type with a descriptive approach. The sampling technique used was purposive sampling technique on 3 grade 8 students as primary subjects. Data collection was done by observation and structured interviews. The data analysis technique used the Miles and Huberman model. The results showed that the most common types of verbal bullying found in this study were name calling, reproach and cruel criticism. The results also show that the form of resilience that victims of verbal bullying have is to fight back, cry and ignore. Efforts that can be given to increase resilience and self-confidence and self-esteem of victims of verbal bullying with group counseling through CBT (Cognitive Behavioral Therapy) techniques and coping mechanisms.